Stres kerja pada anggota kepolisian di Jawa Timur: Bagaimana peranan makna kerja? (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2021)
This study aims to determine the relationship between the meaning of work with job stress on police officers in East Java. The hypothesis in this study is that there is a negative relationship between the meaning of work and job stress. The subjects in this study were 123 participants. The data collection method used a work stress scale, a work meaning scale and a social support scale compiled by researchers using the Likert model. Data retrieval is done through google forms. Hypothesis testing using Spearman Rho'. Hypothesis testing shows that there is a significant relationship between the meaning of work and job stress. The effective contribution of the variable meaning of work and social support to work stress is indicated by the R2 value of 29%. The implications of this research are expected to be able to help police institutions by developing programs to increase the meaning of work for the police in order to reduce work stress. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara makna kerja dengan Stres kerja pada anggota kepolisian di Jawa Timur. Hipotesis pada penelitian ini yaitu ada hubungan yang negatif antara makna kerja dengan stres kerja. Subyek pada penelitian ini sebanyak 123 Partisipan. Metode pengumpulan data menggunakan skala stres kerja, skala makna kerja dan skala dukungan sosial yang disusun peneliti dengan model likert. Pengambilan data dilakukan melalui google formulir. Pengujian hipotesis menggunakan spearman rho’. Pengujian hipotesis menunjukkan adanya hubungan yang signifikan antara makna kerja dengan Stres kerja. Sumbangan efektif variabel makna kerja dan dukungan sosial terhadap Stres kerja ditunjukkan dengan nilai R2 yaitu 29 %. Implikasi dari penelitian ini diharapkan dapat membantu institusi kepolisian dengan mengembangan program-program untuk meningkatkan pemaknaan kerja pada polisi agar dapat mereduksi stres kerja.